2016
DOI: 10.1002/humu.23037
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Error of Cobalamin Metabolism Associated with the Intracellular Accumulation of Transcobalamin-Bound Cobalamin and Mutations inZNF143, Which Codes for a Transcriptional Activator

Abstract: Vitamin B12 (cobalamin, Cbl) cofactors adenosylcobalamin (AdoCbl) and methylcobalamin (MeCbl) are required for the activity of the enzymes methylmalonyl-CoA mutase (MCM) and methionine synthase (MS). Inborn errors of Cbl metabolism are rare Mendelian disorders associated with hematological and neurological manifestations, and elevations of methylmalonic acid and/or homocysteine in the blood and urine. We describe a patient whose fibroblasts had decreased functional activity of MCM and MS and decreased synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…HCFC1 encodes for a transcriptional co-activator that regulates genes important for metabolism and proliferation (12). It is suggested that HCFC1 binds to and regulates the expression of >5000 different genes (18), with various different interacting partners including THAP11 (13) and ZNF143 (49), where mutation of either can cause a cblX like disorder (16,50).…”
Section: Discussionmentioning
confidence: 99%
“…HCFC1 encodes for a transcriptional co-activator that regulates genes important for metabolism and proliferation (12). It is suggested that HCFC1 binds to and regulates the expression of >5000 different genes (18), with various different interacting partners including THAP11 (13) and ZNF143 (49), where mutation of either can cause a cblX like disorder (16,50).…”
Section: Discussionmentioning
confidence: 99%
“…Control of the cell cycle by HCFC1 has been shown to require formation of a complex with the transcription factors THAP domain‐containing protein 11 (THAP11) and zinc finger protein 143 (ZNF143) . Indeed, mutation of both THAP11 and ZNF143 has been shown to result in loss of MMACHC expression and clinical Cbl deficiency, thus demonstrating that this complex is also involved in MMACHC expression. This provides a link between Cbl cofactor synthesis and cell growth and proliferation, which connects the methionine and one‐carbon cycles as well (see below).…”
Section: Allosteric Genetic and Epigenetic Regulationmentioning
confidence: 99%
“…Wei et al (2016) have found that ZNF143 expression can enhance the metastasis of gastric cancer cells, indicating that ZNF143 can be a drug target for the treatment of gastric cancer. The reduction in ZNF143 expression eventually leads to the cobaltamine transport protein not effectively transporting cobalamin (Pupavac et al, 2016). The expression patterns of ZNF143 and ZNF281 in serous borderline ovarian tumors (SBOTs) and low-grade epithelial ovarian carcinomas (EOCs) play a key role in cancer invasion, metastasis formation, and chemotherapy resistance (Sadlecki et al, 2019).…”
Section: Potential Drug Design Targetmentioning
confidence: 99%